Exploring L2 Speaking Motivation Among EFL Pre-Service Teachers: A Comparative Study - Isad Sufi Haiyyat; Moh. Hasbullah Isnaini (English Teaching Journal : A Journal of English Literature, Language and Education, 2025)
One of the factors which affects learners’ speaking ability is their foreign language (L2) speaking motivation. This study investigated the pre-service L2 speaking motivation between 2024 and 2025 batch at one of public universities in Indonesia. Using a comparative study, the study involved 110 pre-service teachers (PST), 55 each batch from whom the researcher gained information about L2 speaking motivation using L2 speaking motivation scale. Prior to data analysis, the researcher conducted normality and homogeneity tests to make sure that they were normally distributed. The result of the t-test indicated that there was significant difference between 2024 and 2025 batch in terms of L2 speaking motivation since the gained p-value was .028 which is lower than the set p- value, .05 with mean difference of 2.96 indicating 2025 batch were more motivated than its counterparts, 2024. This finding explains that duration of study does not affect the level of motivation which might be influenced by the complexity of speaking tasks or activities. Since this is a cross-sectional study, it cannot detect the real problem faced by the L2 learners, which needs longitudinal and in depth to find.